2021
DOI: 10.3390/coatings11010046
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Nucleation and Growth Mechanism of Aluminum on AZ31 Magnesium Alloys

Abstract: In this study, the nucleation and growth kinetics behavior of aluminum (Al) were investigated in the Choline-chloride (ChCl)-urea deep eutectic solvent (DES) ionic liquids. The studies of cyclic voltammetric and chronoamperometry demonstrated that the electrodeposition process of Al was controlled by three-dimensional progressive nucleation and instantaneous nucleation. And the growth of nuclei is a diffusion-controlled process. The diffusion coefficient of Al ions was calculated at 343 K, that is, 1.773 × 10−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Cvetkovic and coworkers have shown that using DES to control the electrodeposition of aluminum (Al) with Al grains varied in size from nano- to micro-meters [ 149 ]. The usage of DES-based ChCl-U for the electrodeposition of aluminum was addressed [ 150 , 151 ]. The nucleation and growth of Al were studied in ChCl-U [ 151 ].…”
Section: Design Strategy and Application Of Des For Nanomaterials Fab...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cvetkovic and coworkers have shown that using DES to control the electrodeposition of aluminum (Al) with Al grains varied in size from nano- to micro-meters [ 149 ]. The usage of DES-based ChCl-U for the electrodeposition of aluminum was addressed [ 150 , 151 ]. The nucleation and growth of Al were studied in ChCl-U [ 151 ].…”
Section: Design Strategy and Application Of Des For Nanomaterials Fab...mentioning
confidence: 99%
“…The usage of DES-based ChCl-U for the electrodeposition of aluminum was addressed [ 150 , 151 ]. The nucleation and growth of Al were studied in ChCl-U [ 151 ]. In another work, gold and silver were recycled from anodic slime using choline chloride and ethylene glycol (molar ratio of 1:2) [ 152 ].…”
Section: Design Strategy and Application Of Des For Nanomaterials Fab...mentioning
confidence: 99%
“…Zhang et al . demonstrated the nucleation and growth mechanism of Al in the ChCl–urea deep eutectic solvent ionic liquid . Xu et al investigated the anodic behavior of Mg in the acidic AlCl 3 –EMIC ionic liquid .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al demonstrated the nucleation and growth mechanism of Al in the ChCl−urea deep eutectic solvent ionic liquid. 13 Xu et al investigated the anodic behavior of Mg in the acidic AlCl 3 − EMIC ionic liquid. 14 Tang et al performed zinc (Zn) immersion pretreatment for the AZ91D Mg alloy with the bipolar current pulse technique to increase the bonding force and anticorrosion ability of the Al coating.…”
Section: Introductionmentioning
confidence: 99%